Efficient enhanced routing protocal and accurate tracking mechanism for monitoring environmental changes using multihop wireless sensor networks - Mohammed, Omar Fouad (2019)
The advances in the wireless communication industry have paved the way for wide utilization of Wireless Sensor Networks (WSNs) applications. The main application of WSNs is environmental monitoring where sensors are cooperatively used to monitor physical or environmental events and report their sensed data to a central unit for processing, analysis and decision making. In other words, due to the distinctive capabilities of sensors to monitor different environmental parameters, WSNs can provide better solutions for monitoring abnormal events such as fire incident, gas leak and car accident. However, the existing WSN-based detection and tracking systems still suffer from efficiency and suitability for real-time data traffic control and management issues. These issues include network congestion, high energy consumption and communication overhead. In addition, the systems have poor performance in terms of tracking accuracy and prediction of the event’s future location, which means the systems do not provide accurate mechanism for tracking the event’s development. In order to deal with the above mentioned issues, this study presents environmental monitoring system to enhance network traffic in the sense of sensed data delivery and to ensure the accuracy of fire event detection and tracking in WSN. The proposed system relies on efficient enhanced routing protocol and accurate tracking mechanism. The enhanced protocol is based on cluster head selection method that aims to reduce the energy dissipation in the cluster construction procedure and prolong the network lifetime. Besides, a dynamic data transmission strategy is also presented by which the load of forwarding the sensed data packets is balanced among the cluster heads and the forwarding nodes in the data transmission procedure. Accordingly, the energy-hole problem is mitigated which in turn the energy efficiency and the throughput of the WSN are improved. By utilizing the communication overhearing in WSNs and some statistical concepts, a tracking mechanism to ensure the accuracy of the monitoring system in estimating the fire spread is thus designed. The simulation results show that, compared with the common routing protocol, the enhanced protocol decreases the energy consumption by about 30%. While in two different simulation tests, the network lifetime is increased by about 30% and 40% respectively. Moreover, more 1.11E+09 bits of data were received by the base station for the last 40 rounds of the network life cycle which indicates that the network throughput is improved. The dynamic data transmission strategy increases the network lifetime by about 22% compared to other existing method and the tracking mechanism is capable of accurately estimating the fire development.